The Position of The Honorary Council of The Constitutional Court in the Indonesian Legal Order - Juanda Juanda; Nanda Dwi Rizkia (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
ABSTRACT This research is qualitative research with a normative approach. The data that researchers use in this article is secondary data that researchers obtained from various credible sources such as legal regulations, books, articles, scientific and various other sources. The data that the researchers used were analyzed using three legal analysis techniques, namely normative legal analysis techniques, historical legal analysis techniques, and telelogical legal analysis techniques. The result in this article show The Honorary Council of the Constitutional Court has existed since the enactment of Law no. 24 of 2003, namely Article 23 paragraph (3), which states that;